Antimicrobial activity and the presence of virulence factors and bacteriocin structural genes in Enterococcus faecium CM33 isolated from ewe colostrum - Nami, Yousef; Haghshenas, Babak; Haghshenas, Minoo; Yari Khosroushahi, Ahmad (Frontiers in Microbiology, 2015)
Abstract Screening of lactic acid bacteria isolated from ewe colostrum led to the identification and isolation of Enterococcus faecium CM33 with interesting features, such as high-survival rates under acidic or bile salt conditions, high tolerance to the simulated gastrointestinal condition, and high adhesive potential to Caco-2 cells. According to the inhibition of pathogen adhesion test results, this strain could reduce more than 50% adhesion capacity of Escherichia coli, Shigella flexneri, Klebsiella pneumoniae, Listeria monocytogenes, and Staphylococcus aureus to Caco-2 cells. Based on the antibiotic sensitivity test findings, E. faecium CM33 was susceptible to gentamycin, vancomycin, erythromycin, ampicillin, penicillin, tetracycline, and rifampicin, but resistant to chloramphenicol, clindamycin, and kanamycin. Upon the assessment of the virulence determinants for E. faecium CM33, this strain was negative for all tested virulence genes. Furthermore, the genome of this strain was evaluated for the incidence of the known enterocin genes by specific PCR amplification, and the genes encoding enterocins A, 31, X, and Q were discovered. The findings of this study showed that the strain E. faecium CM33 could be considered a valuable nutraceutical, and it can be introduced as a new potential probiotic.